1991
DOI: 10.1093/ndt/6.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Carbamylated Haemoglobin, Urea Kinetic Modelling and Adequacy of Dialysis in Haemodialysis Patients

Abstract: Urea kinetic modelling (UKM) has increasingly been used for assessing adequacy of dialysis and protein nutritional status of dialysis patients. Using a precise HPLC method we developed, we measured carbamylated haemoglobin (CarHb) values in 20 stable twice-weekly dialysed patients and attempted to correlate their CarHb values with their UKM-derived indices. Based on these indices, 11 patients were found to have been adequately dialysed with sufficient protein intake, three patients were adequately dialysed but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…where C1, C2 and C3, respectively, represent the pre-BUN, the post-BUN and the pre-BUN at the next HD (mg/dl); t d represents duration of dialysis (min), and t o represents the interdialytic period (min) [11]. The nPCR value was determined by the method of Depner and Cheer [12].…”
Section: Methodsmentioning
confidence: 99%
“…where C1, C2 and C3, respectively, represent the pre-BUN, the post-BUN and the pre-BUN at the next HD (mg/dl); t d represents duration of dialysis (min), and t o represents the interdialytic period (min) [11]. The nPCR value was determined by the method of Depner and Cheer [12].…”
Section: Methodsmentioning
confidence: 99%
“…15 Carbamylated haemoglobin provides a greater intra-patient stability in the assessment of uraemia that is not affected by a single haemodialysis treatment, and takes some 2 weeks or more to decline following successful renal allograft transplantation. 18 It has a possible role in the clinical management of patients with chronic renal failure similar to the way glycosylated haemoglobin is used in the monitoring of diabetic patients. 15 Because both carbamylation and glycation reactions involve the free amino groups of the protein, especially the terminal valine residues in the case of haemoglobin, one should consider the possible interference between the two reactions.…”
Section: ±5mentioning
confidence: 99%
“…Stim et al [20], using HPLC – in contradistinction to Smith et al [4] who used gas chromatography – found a mean of 106 (SD 7) in hemodialysis patients. Kwan et al [21] reported the results in 20 patients; they divided their patients according to the adequacy of their dialyses and found in 11 with adequate dialysis that carbamylated hemoglobin was elevated (142 ± 29 µg of valine hydantoin per gram of hemoglobin), but in 6 of the underdialyzed group on hemodialysis the concentration was significantly higher (197 ± 30; p = 0.002). We have found in a group of adequately dialyzed hemodialysis patients, in whom the incubation was done at a carefully controlled 90°C, an elevated figure (89.6 ± 22) but lower than the values of Kwan et al [7], although our controls at this temperature were similar in value [Berlyne and Caruso, unpubl.…”
Section: Carbamylated Hemoglobin In Renal Diseasementioning
confidence: 99%
“…Davenport et al [12] studied 55 regular dialysis patients and like Kwan et al [21] found elevated carbamylated hemoglobin levels in both well-dialyzed and poorly dialyzed patients (120 ± 8 vs. 99 ± 7; p < 0.01).…”
Section: Carbamylated Hemoglobin In Renal Diseasementioning
confidence: 99%
See 1 more Smart Citation